Hemoglobin A1c predicts hemorrhagic transformation and poor outcomes after acute anterior stroke. (31st July 2018) - Zhang, G.; He, M.; Xu, Y.; Li, X.; Cai, Z.; Guo, Z.; Meng, P.; Ji, N.; He, X.; Pang, L.
Abstract : Background and purpose: Hemorrhagic transformation (HT) is a major complication of acute ischaemic stroke that is potentially related to clinical deterioration. The objective of this study was to assess whether chronic hyperglycemia is a predictive factor of HT in patients with acute anterior stroke. Methods: Patients with acute anterior stroke were included in this study. Hemoglobin A1c (HbA1c) was measured in the morning after hospitalization. HT was detected by computed tomography scans or gradient echo magnetic resonance imaging performed 4 (±2) days after onset. Univariate and multivariate logistic regression analyses were used to assess the risks for HT and short‐term outcomes. Results: Of the 426 patients included, 93 (21.8%) had HT: 61 (14.3%) presented with hemorrhagic infarction and 32 (7.5%) presented with parenchymal hematoma. A total of 54 patients received thrombolytic treatment and 18 (33.3%) were found to have HT. In the multivariate analysis, HbA1c [odds ratio (OR), 1.294; 95% confidence interval (CI), 1.097–1.528], infarction size (OR, 3.358; 95% CI, 1.748–6.449) and thrombolytic therapy (OR, 3.469; 95% CI, 1.757–6.847) were predictors of HT. The predictive effect of HbA1c on HT was still observed in both groups when patients were stratified according to the levels of fasting blood glucose. HbA1c was found to be a predictor of poor outcomes in the multilogistic regression analysis (OR, 1.482; 95% CI, 1.228–1.788). Conclusions: Higher HbA1c was independently related to HT and poor neurological outcomes in patients with ischaemic stroke. These findings have significant implications for the treatment of diabetes and glucose management in patients with diabetes mellitus and/or acute ischaemic stroke. Abstract : Clickhere to view the accompanying paper in this volume.